The Influence of Leadership Style and Organizational Culture on The Performance of Board of Representatives EmployeesRegional People of Jeneponto Regency - Rahmat Hidayat; Ramli, Anwar; Kurniawan, Agung Widhi (Economos : Jurnal Ekonomi dan Bisnis, 2023)
Employee performance can be seen from the aspects of quality, quantity, time and cooperation in achieving strategic goals. This study aims to determine whether leadership style and organizational culture have a significant effect on the performance of employees of the Regional People's Representative Council of Jeneponto Regency. The sampling technique uses simple random sampling (random sample) with a total of 35 people. Data collection was carried out using observation methods, questionnaires and documentation. The data analysis techniques used are simple linear regression analysis, normality test, t-test (partial) and coefficient of determination (R2). The results of the study after the data was processed with Statistical for Product and Service Solution (SPSS) showed that the results of analysis and hypothesis testing showed that Leadership Style had a significant effect on employee performance while Organizational Culture did not affect employee performance and both simultaneously affected employee performance.